WiMAX capacity estimation through channel characteristic simulation - Harng G.K.; Kiong T.S.; Koh J.; Yap D. (2023)
WiMAX (IEEE 802.16) is a broadband wireless access technology that enables convergence of mobile and fixed broadband networks through scalable OFDMA (Orthogonal Frequency Division Multiple Access) technology. This paper presents the modeling of WiMAX propagation channel statistically. WiMAX channel performance of different frequency bands applied in Asia Pacific region are investigated and evaluated. WiMAX system capacity under different channel characteristics derived analytically, and also the optimal SINR can achieved under different frequency bands, a CDF graph of SINR is plotted to simulate the result and also the probability of the CDF is analysis. 2008 IEEE.